Old Henry - Blos, Joan W.; Gammell, Stephen (New York : Mulberry Books, 1990)
Henry's neighbors are scandalized that he ignores them and l his property get run down, until they drive him away and find themselves missing him.
Keywords: Neighborliness -- Fiction; Stories in rhyme